Is continuous positive airway pressure (CPAP) a new standard of care for type 1 respiratory failure in COVID-19 patients? A retrospective observational study of a dedicated COVID-19 CPAP service. Issue 1 (5th July 2020) - Nightingale, Rebecca; Nwosu, Nneka; Kutubudin, Farheen; Fletcher, Tom; Lewis, Joe; Frost, Frederick; Haigh, Kathryn; Robinson, Ryan; Kumar, Ayesha; Jones, Gareth; Brown, Deborah; Abouyannis, Michael; et al.
Abstract : The aim of this case series is to describe and evaluate our experience of continuous positive airway pressure (CPAP) to treat type 1 respiratory failure in patients with COVID-19. CPAP was delivered in negative pressure rooms in the newly repurposed infectious disease unit. We report a cohort of 24 patients with type 1 respiratory failure and COVID-19 admitted to the Royal Liverpool Hospital between 1 April and 30 April 2020. Overall, our results were positive; we were able to safely administer CPAP outside the walls of a critical care or high dependency unit environment and over half of patients (58%) avoided mechanical ventilation and a total of 19 out of 24 (79%) have survived and been discharged from our care.